PENERAPAN MODEL PEMBELAJARAN PBL DENGAN MEDIA VIDEO BERBASIS ISU TERKINI KEBHINNEKAAN UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR LOGIS PESERTA DIDIK KELAS X-8 SMA NEGERI 7 KOTA KEDIRI - Fajar Danang Dewantara; Budiono (Jurnal Tinta: Jurnal Ilmu Keguruan dan Pendidikan, 2023)
The purpose of this study was to improve the ability to think logically through video media based on current issues regarding Diversity with the Problem Based Learning model for students in class X-8 SMA Negeri 7 Kota Kediri in the 2023/2024 Academic Year. This research is a Classroom Action Research, and each cycle consists of planning, implementing, acting, observing, and reflecting. Techniques for collecting data in this study are documentation, observation, and tests. The validity of the data used is content validity, namely content validation. The data analysis technique uses a comparative descriptive model analysis technique. The results of this study indicate that through the Problem Based Learning model with video media based on current issues can improve the ability to think logically for students in class X-8 SMA Negeri 7 Kediri in Civics learning, based on the results of this class action research there is an increase in the average value in diversity material is 85 and 90 for the first and second cycles.